Accountability For Immediate Assistance In Village Fund (Case Study in Lesmana Village, Banyumas Regency) - Herliana, Herliana; Rusmana, Oman (Universitas Muhammadiyah Sorong, 2021)
Pandemic Â Covid-19 has an impact on decreasing community income, direct cash assistance sourced from village funds is one solution so that the poor can survive their prime. The research objective was to see how the village of Lesmana relocated village funds into direct cash assistance, as well as to see the accountability of the Village Fund BLT management. This type of qualitative research with case studies, the data used are primary data from observations, interviews, questionnaires and secondary data from literature studies. The results showed that the relocation of village funds to direct cash assistance in the village of Lesmana was in accordance with existing regulations, as well as in terms of management it was carried out quite accountably.